2003
DOI: 10.1016/j.adolescence.2003.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Violence exposure in real‐life, video games, television, movies, and the internet: is there desensitization?

Abstract: It is believed that repeated exposure to real‐life and to entertainment violence may alter cognitive, affective, and behavioral processes, possibly leading to desensitization. The goal of the present study was to determine if there are relationships between real‐life and media violence exposure and desensitization as reflected in related characteristics. One hundred fifty fourth and fifth graders completed measures of real‐life violence exposure, media violence exposure, empathy, and attitudes towards violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
233
1
18

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(261 citation statements)
references
References 72 publications
(73 reference statements)
9
233
1
18
Order By: Relevance
“…Using a similar survey approach with 150 fourth and fifth graders, greater long-term exposure to violent video games was associated with lower empathy and stronger proviolence attitudes. [7] In another study, no difference was found in immediate empathic or aggressive responding after 66 five to twelve year old children played a violent or nonviolent video game. However, again using the established category system, a long-term preference for violent video games was associated with lower empathy.…”
Section: Violent Video Games and Desensitizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a similar survey approach with 150 fourth and fifth graders, greater long-term exposure to violent video games was associated with lower empathy and stronger proviolence attitudes. [7] In another study, no difference was found in immediate empathic or aggressive responding after 66 five to twelve year old children played a violent or nonviolent video game. However, again using the established category system, a long-term preference for violent video games was associated with lower empathy.…”
Section: Violent Video Games and Desensitizationmentioning
confidence: 99%
“…However, if an individual becomes desensitized to violence, then the moral reasoning processes that could inhibit aggression may be bypassed. [7] As a real life example, it has been reported that the United States army has used violent video games to desensitize soldiers during combat training. [10] It is interesting that the American army disseminates its own video game, America's Army, to potential recruits.…”
Section: Desensitization To Violence Definedmentioning
confidence: 99%
See 1 more Smart Citation
“…The first game that was considered to be controversial, Death Race, was published as an arcade game by Exidy in 1976 (Gonzalez, 2004). Computer and video games, and their possible effects on players, have been studied in many fields of scientific literature, with areas of focus including whether games with violent content increase aggression or violence (Anderson & Ford, 1986;Cooper & Mackie, 1986;Funk et al, 2002;Gentile, Lynch, Linder, & Walsh, 2004;Sherry, 2001); whether these games lead to desensitization (Funk, Baldacci, Pasold, & Baumgardner, 2004), real aggression, or violence; the physiological responses to playing computer and video games (van Reekum et al, 2004); addiction (Phillips, Rolls, Rouse, & Griffiths, 1995;Salguero & Moran, 2002); and the use and efficacy of computer and video game ratings (Haninger & Thompson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pour faciliter ce réflexe, la dimension répétitive des jeux vidéo augmente le seuil de tolérance à la violence chez le joueur (Hartmann et Vorderer, 2010). Par ailleurs, contrairement à la violence au cinéma, à la télévision et sur Internet, la violence dans les jeux vidéo provoque une baisse de l'empathie chez le joueur (Royal, 1999 ;Funk et al, 2004). La pratique des jeux vidéo violents semble donc particulièrement efficace pour désensibiliser le joueur (Funk et al, 2004), en ce qu'elle atténue ou élimine « des réponses cognitives, émotionnelles et behavioristes » (Rule et Ferguson, 1986).…”
Section: Effets Psychologiquesunclassified